2020
DOI: 10.1002/ddr.21737
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial hepatocyte growth factor receptor agonist stimulates hepatocyte proliferation and accelerates liver regeneration in a partial hepatectomy rat model

Abstract: Hepatocyte growth factor (HGF) is central to liver regeneration. The Internalin B (InlB) protein is a virulence factor produced by the pathogenic bacterium Listeria monocytogenes. InlB is known to mimic HGF activity by interacting with the HGF receptor (HGFR) and activating HGFR‐controlled signaling pathways. We expressed and purified the HGFR‐binding InlB domain, InlB321/15, cloned from the fully virulent clinical L. monocytogenes strain. HGFR and Erk1/2 phosphorylation was determined using Western blotting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
3
0
2
Order By: Relevance
“…37 In the PHx liver, administration of anakinra, an IL-1 receptor antagonist, upregulated proliferating cell nuclear antigen (PCNA) compared with the vehicle-giving group. 38 Kalinin et al 39 demonstrated that treatment with the protein internalin B generated from Listeria monocytogenes , which mimics HGF, activated extracellular signal-regulated kinase and upregulated expression of cyclin D1 and CDK 2, 4 in rats with PHx. Wnt/β-catenin signaling is also shown to contribute to liver mass recovery.…”
Section: Therapeutic Strategies For Liver Regeneration After Partial ...mentioning
confidence: 99%
“…37 In the PHx liver, administration of anakinra, an IL-1 receptor antagonist, upregulated proliferating cell nuclear antigen (PCNA) compared with the vehicle-giving group. 38 Kalinin et al 39 demonstrated that treatment with the protein internalin B generated from Listeria monocytogenes , which mimics HGF, activated extracellular signal-regulated kinase and upregulated expression of cyclin D1 and CDK 2, 4 in rats with PHx. Wnt/β-catenin signaling is also shown to contribute to liver mass recovery.…”
Section: Therapeutic Strategies For Liver Regeneration After Partial ...mentioning
confidence: 99%
“…Отсу тствие внешней опорной поверхности при формировании неприкрепленных агрегатов является важным отличием, указывающим на ограничения существующих моделей биопленок in vitro [10]. Скорее такие автоагрегаты, сформированные одним видом бактерий и не прикрепленные к поверхности, напоминают флокулы, хорошо известные микробиологам, изучающим поведение бактерий в естественных водоемах.…”
Section: обсуждение полученных данныхunclassified
“…Как и биопленки, неприкрепленные агрегаты обеспечивают повышенную устойчивость к противомикробным препаратам [5]. С другой стороны, такие особенности, как потребность в бактериальной подвижности, состав матрикса и механизмы регуляции, могут различаться между неприкрепленными агрегатами и классическими биопленками [10].…”
Section: обсуждение полученных данныхunclassified
“…C-Met-deficient mice showed a higher mortality rate after 70% PH ( 60 ), suggesting the function of HGF/Met in liver regeneration. Listeria monocytogenes, a pathogenic bacterium can be found in various kinds of food, can enhance the effect of HGF through producing bacterial HGF receptor agonist InlB321/15 and thus promote liver regeneration after 70% PH ( 61 ). Lactiplantibacillus plantarum AR113 administration showed decline of phosphatidylethanolamine (PE), phosphatidylcholine (PC), phosphatidyl serine (PS), and lysophosphatidyl choline (LysoPC) levels in the serum of the rats and increase HGF secretion in liver after 70% PH ( 62 ).…”
Section: Gut Microbiota Affects Liver Regeneration By Modulating Cruc...mentioning
confidence: 99%